The illness experience of middle‐aged men with oral cancer. Issue 23 (December 2013) - Cheng, Ching‐Hui; Wang, Tsae‐Jyy; Lin, Yu‐Ping; Lin, Hung‐Ru; Hu, Wen‐Yu; Wung, Shin‐Huey; Liang, Shu‐Yuan
Abstract : Aims and objectives: To explore the essence of the illness experiences of middle‐aged men with oral cancer. Background: Having oral cancer creates great challenges in the lives of middle‐aged men and their families. Understanding patients' experiences provides a sound basis for patient‐centred and individualised care. Research is limited regarding the illness experience of middle‐aged men with oral cancer with regard to facing both the invasion of disease and the responsibilities of middle age. Design: A phenomenology approach was used. Methods: Nine men diagnosed with oral cancer within one year were recruited during 2009 and 2010. Data were collected through individual in‐depth interviews and analysed using Colaizzi's phenomenological analysis procedures. Results: The following five themes emerged from the patterns of categorised interview data: the psychological journey in facing oral cancer, the question of how patients can control their disease as well as the sequelae of cancer treatment, the continuous disturbance and turmoil resulting from the disease, the appreciation of the support from family and friends, and the ability to learn to actively face the future. Conclusions: Patients with oral cancer experienced tremendous physical, psychosocial and financial challenges. Although burdened with multiple stressors, these middle‐aged men were able to learn from their experiences and exhibit positive growth in life. Relevance to clinical practice: Patients with oral cancer have to constantly adjust to the impact of their disease. The study results may serve as a reference for improving clinical practice and the quality of care among patients with oral cancer. Cancer care is multidimensional and holistic. Healthcare professionals should develop a set of plans by which patients receive complete medical care and support, as well as assistance from professionals and family members, as their treatment progresses to help patients face the challenges of cancer.